Development of Customized Distribution Automation System (DAS) for Secure Fault Isolation in Low Voltage Distribution System - Ab Ghani, Mohd Ruddin; Mat Hanafiah, Mohd Ariff (InTech, 2010)
A Customized SCADA based RTU for service substation and customer service substation is developed by using the open loop concept for the distribution networks. Currently, the SCADA system in the low distribution system implemented by TNB only focuses on alarm monitoring. SSO has to operate the control functions at the HMI side. The operator needs to analyze the situation and to make appropriate actions. A Customized SCADA is built to provide automatic fault isolation for low distribution system. In this chapter, the proposed methodology is summarized with the experimental results and conclusion based on the results is also highlighted.